2016
DOI: 10.18869/acadpub.jnms.3.4.37
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perception of the ethical climate in the Iranian hospital environment

Abstract: Background and Purpose: Ethical climate is hinged upon organizational culture, rules, and policies; nurses' perception of this concept varies according to the ward they are working on and the new rules of the treatment system. This can exert adverse impact on their care method and performance. Thus, this study aimed to determine nurses' perceptions of the ethical climate governing the hospital environment. Methods: This descriptive, cross-sectional study was conducted on 168 nurses working in a teaching hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
17
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
7
17
3
2
Order By: Relevance
“…Perhaps the reason for this difference in working conditions and organizational culture in Iran hospitals with other countries. According to Shafipour et al (2016) findings, in Iran, the average score of ethical climate was 3.5 (8) which is largely consistent with the results of the present study. Accordingly, the above average of ethical climate in Iran can be promising and similar results in Iranian studies indicate that the factors affecting the ethical climate of nurses working environment in Iran are similar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perhaps the reason for this difference in working conditions and organizational culture in Iran hospitals with other countries. According to Shafipour et al (2016) findings, in Iran, the average score of ethical climate was 3.5 (8) which is largely consistent with the results of the present study. Accordingly, the above average of ethical climate in Iran can be promising and similar results in Iranian studies indicate that the factors affecting the ethical climate of nurses working environment in Iran are similar.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the fact that the services provided in the health system require interdisciplinary collaboration, this finding is alarming and it seems that nursing and medical services are provided in separate packages. The results of Shafipour et al (2016) and Jolaee et al (2013) in Iran suggest the appropriateness of the relationship between doctors and nurses (8 and 11). In such situation, not only the quality of care affected, the probability of complications such as the moral distress increases in doctors and nurses (12).…”
Section: Discussionmentioning
confidence: 91%
“…Even though studies conducted over several years in diverse areas of nursing practice have shown that nurses face serious ethical challenges, researchers and policy-makers who study the work environment use an ethics lens to look at workplace problems (44). Previous research has shown that the moral climates of Iranian hospitals are not encouraging, and the reward and punishment systems did not support moral practice (42,(45)(46)(47). In this situation, nurses cannot recognize and solve moral issues (48,49).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that the moral climates of Iranian hospitals are not encouraging, and the reward and punishment systems did not support moral practice (40,(43)(44)(45). In this situation, nurses cannot recognize and solve moral issues (46,47).…”
Section: Discussionmentioning
confidence: 98%